Exploring the effects of pH, dimerization and disulfide bonding on the dynamics of WT and artemisinin-resistant mutants of Plasmodium falciparum Kelch 13 - Bebey, Reine Deborah (Rhodes University, 2026)
Embargo applied. Embargo period to expire in October of 2027.
Keywords: Uncatalogued